Targeting specific HATs for neurodegenerative disease treatment: translating basic biology to therapeutic possibilities - Pirooznia, Sheila K.; Elefant, Felice (Frontiers in Cellular Neuroscience, 2013)
Dynamic epigenetic regulation of neurons is emerging as a fundamental mechanism by which neurons adapt their transcriptional responses to specific developmental and environmental cues. While defects within the neural epigenome have traditionally been studied in the context of early developmental and heritable cognitive disorders, recent studies point to aberrant histone acetylation status as a key mechanism underlying acquired inappropriate alterations of genome structure and function in post-mitotic neurons during the aging process. Indeed, it is becoming increasingly evident that chromatin acetylation status can be impaired during the lifetime of neurons through mechanisms related to loss of function of histone acetyltransferase (HATs) activity. Several HATs have been shown to participate in vital neuronal functions such as regulation of neuronal plasticity and memory formation. As such, dysregulation of such HATs has been implicated in the pathogenesis associated with age-associated neurodegenerative diseases and cognitive decline. In order to counteract the loss of HAT function in neurodegenerative diseases, the current therapeutic strategies involve the use of small molecules called histone deacetylase (HDAC) inhibitors that antagonize HDAC activity and thus enhance acetylation levels. Although this strategy has displayed promising therapeutic effects, currently used HDAC inhibitors lack target specificity, raising concerns about their applicability. With rapidly evolving literature on HATs and their respective functions in mediating neuronal survival and higher order brain function such as learning and memory, modulating the function of specific HATs holds new promises as a therapeutic tool in neurodegenerative diseases. In this review, we focus on the recent progress in research regarding epigenetic histone acetylation mechanisms underlying neuronal activity and cognitive function. We discuss the current understanding of specific HDACs and HA